ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL MODERASI PADA PERUSAHAAN BATUBARA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Agnes Oktavia Pramitha; Yuniningsih Yuniningsih (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This research aims to analyze the effect of economic value added, inflation, net profit margin, and dividend yield on stock returns with company value as a moderating variable either partially or simultaneously. The research scope is coal sub-sector companies that is listed on the Indonesia stock exchange (BEI) for the period 2015-2021, using purposive sampling technique, 6 companies were obtained as research samples. The analysis technique that is used are multiple linear regression analysis and moderate regression analysis. The results are partially only the Net profit margin variable that has significant effect on stock returns, while the Economic value added, inflation, and dividend yield variables have no effect on stock returns. In addition, firm value as a moderating variable proved unable to strengthen or weaken the relationship between Economic value added, Inflation, Net profit margin, and Dividend yield on stock returns. Simultaneously, all variables have no effect on Stock Return.